A new 'sticking' coating method for the in situ formation of nanofiber networks on micrometer to millimeter-sized surfaces. Issue 14 (23rd March 2018) - Tenjimbayashi, Mizuki; Yoshikawa, Ryohei; Park, Jun-Yong; Kobayashi, Yuta; Monnai, Yasuaki; Muto, Jun; Shiratori, Seimei
Abstract : A simple and versatile method is developed to form nanofiber coatings in situ on micrometer to millimeter-sized surface via advanced electrospinning technique. The technique overcomes conventional nanofiber coating difficulties of downscaling coating objects. Abstract : A simple versatile method to form a nanofiber coating in situ on micrometer to millimeter-sized surfaces is developed. A fiber-filled porous sheet is designed by electrospinning a dense polymer solution on a patterned PET/aluminum alloy collector. By sticking the small area surface onto a fiber-filled porous sheet, a nanofiber-coated small area surface is obtained, which overcomes conventional nanofiber coating difficulties.